2021
DOI: 10.1177/1060028021999821
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Phenobarbital for Alcohol Withdrawal Syndrome: A Focused Literature Review

Abstract: Objective: To review the literature describing the use of adjunctive phenobarbital in the treatment of severe alcohol withdrawal syndrome (AWS). Data Sources: PubMed and EMBASE were searched using the following terms: phenobarbital, adjunct, refractory or treatment resistant, severe or complicated, and alcohol withdrawal delirium or alcohol withdrawal seizures. Study Selection and Data Extraction: The search was limited to randomized controlled trials (RCTs) and cohort studies published in English. Data Synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Despite warnings from the World Health Organization, alcohol consumption is expected to increase until at least 2025. Hospital admissions for chronic alcohol abusers are particularly dangerous since these patients are at an increased risk of developing life-threatening conditions such as alcohol withdrawal syndrome (AWS) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite warnings from the World Health Organization, alcohol consumption is expected to increase until at least 2025. Hospital admissions for chronic alcohol abusers are particularly dangerous since these patients are at an increased risk of developing life-threatening conditions such as alcohol withdrawal syndrome (AWS) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benzodiazepines are the standard of care for treating alcohol withdrawal syndrome (AWS), but there is growing interest in the United States in re‐utilizing the long‐acting barbiturate, phenobarbital (PB) as an adjunctive or primary medication in severe cases. This is due to PB's potentially favorable pharmacodynamic properties compared to benzodiazepines [1], and a high‐impact 2013 trial demonstrated reduced intensive care unit (ICU) admissions with PB administration in the emergency department (ED) [2]. We found that since then (2013–22) there has been a sixfold (PubMed®) to 11‐fold (Google Scholar™) increase in publications on the topic compared to the prior decade (2003–12).…”
Section: Figurementioning
confidence: 99%
“…Препарати бензодіазепінового ряду є пріоритетними для забезпечення належного її рівня [10]. Багато досліджень повідомляють, що в людей з великим стажем зловживання алкоголю та з наявними попередніми епізодами делірію, формується так званий синдром резистентності до бензодіазепінів [8]. Додаткове використання барбітуратів часто призводить до розвитку гіпотонії та дихальних розладів [7].…”
Section: вступunclassified